Isolation, characterilzation and identification of phosphate solubilizing bacteria from rice-shrimp rotational farming system in salt affected soil areas of the mekong delta of Vietnam - Nghĩa, Nguyễn Khởi; Oanh, Nguyễn Thị Kiều (Vietnam Journal of Biotechnology, 2018)
Phosphorus is the least mobile element in plant and soil contrary to other macronutrients. Phosphorus solubilizing bacteria play role in phosphorus nutrition by enhancing its availability to plants. Aim of study was to deal with isolation, characterization and identification of phosphate solubilizing bacteria (PSBs) from 15 paddy rice soil samples collected in rice–shrimp rotational farming system in salt affected soil areas of the Mekong Delta of Vietnam including Bac Lieu, Ca Mau, Soc Trang, Kien Giang and Ben Tre by using NBRIP media containing 1% NaCl. Concentration of phosphate was determined by method of colometric determination of molybdate. Results showed that 95 isolates indicating potentially as PSBs through a exhibiting of a halo zone happening around bacterial colonies on NBRIP media. Twenty out of ninety five isolates showed their highly phosphate solubilizing ability (>1000 mg.L-1) in the liquid culture. Bacterial strain coded as BL1-10 solubilized maximumly 2044 mg.L-1 phosphate in liquid media after 5 incubation days. The cell number and phosphate solubilizing ability of Bl-10 strain were till good and not affected under environmental coditions like 40oC, salinity range between 0.5 and 5 % NaC and pH range between 3 and 5. Three kinds of trade name fungicides like DA roral, Topsin M và Antracol 70WP did not affect on cell numbers and phosphate solubilizing ability of Bl-10 strain. However, cell numbers and function of phosphate solubilizing ability of this bacterial strain was completely inhibited by Ridomil Gold fungicide. This strain was genetically identified as species of Burkholderia sp. BL1-10 based on results of the 16S rRNA gene sequence analysis. In conclusion, the study suggests the most promising phosphate solubilizing bacteria, Burkholderia sp. BL1-10 can be used as efficient biofertilizer inoculant to promote plant growth.